Explicit technique for teaching writing to students with sociological learning style - Arifuddin Balla (Institut Parahikma Indonesia, 2021)
The objective of this research was to find out the influence of explicit technique in teaching writing to the students whose learning preference is sociological learning style. This research was a pre-experimental study with a pre-test and post-test conducted at English Education Department of UIN (Universitas Islam Negeri) Alauddin with 30 students as respondents. They were divided into two groups: individual sociological learning style (ISLS) and group sociological learning style (GSLS). The data were collected through an essay test and Sociological Learning Styles Inventory. The results of students’ essay tests were analyzed by using SPSS version 20. The data analysis and interpretation indicated: 1) there was a significant difference for students whose learning preference ISLS before and after treatment. 2) there was a significant difference for students whose learning preference GSLS before and after treatment. 3). there was a significant difference for students whose learning preference between ISLS and GSLS before and after treatment. In conclusion, there is no significant difference between students whose learning preference ISLS and ISLS before and after treatment. Sociological learning style does not have any influence on students’ achievement score in teaching writing by using explicit technique. The achievement gained was probably caused by the treatment by using explicit technique. In the end, explicit technique can increase students’ writing ability for both ISLS and GSLS students.